Acoustic Radiation Force Impulse Elastography and Ultrasonographic Findings of Achilles Tendon in Patients With and Without Diabetic Peripheral Neuropathy: A Cross-Sectional Study - İyidir, Özlem Turhan; Rahatlı, Feride Kural; Bozkuş, Yusuf; Ramazanova, Lala; Turnaoğlu, Hale; Nar, Aslı; Tütüncü, Neslihan Başçıl (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aims We aimed to evaluate the elastographic features of Achilles tendon with Acoustic Radiation Force Impulse in patients with and without diabetic neuropathy.Methods According to the presence of peripheral neuropathy, 45 patients with type 2 diabetes were divided into 2 subgroups. Those with peripheral neuropathy were defined as group I (22 patients) and those without peripheral neuropathy were defined as group II (23 patients). A total of thirty age-, gender-, and body mass index-matched healthy individuals were selected as controls. All participants underwent both ultrasonographic and Acoustic Radiation Force Impulse elastographic examination in order to evaluate Achilles Tendon thickness and stiffness.Results Achilles tendon thicknesses were similar between groups (p=0.991). Achilles tendon thicknesses of both patient groups were significantly higher than the control group (group I vs control p=0.01; group II vs control p=0.006). Stiffness values of Achilles tendons were similar between the control group and group II (p=0.993). Shear Wave Velocity was significantly lower in group I than group IIand control group (p<0.001).Conclusion Diabetic patients with neuropathy have thicker and softer Achilles tendon while the elasticity of Achilles tendon in diabetic patients without neuropathy is similar to the healthy controls. Softening of the Achilles tendon may be an early sign of diabetic foot and reveal the patients with a risk of diabetic foot.
Keywords: achilles tendon; stiffness; acoustic radiation force impulse elastography; diabetes mellitus